Variations in earnings growth: evidence from earnings transitions in the NZ Linked Income Survey - Ron Crawford (University of Essex, Institute for Social and Economic Research (ISER), 2009)
This paper uses the New Zealand Linked Income Supplement (LIS) to investigate the annual transitions in hourly earnings of working age individuals over the years 1997 to 2004. I first construct transition matrices for annual changes in weekly and hourly earnings, to enable comparison with previous analyses using New Zealand tax data. I then estimate the determinants of annual changes in hourly earnings using OLS and quantile regressions. Differences in human capital are associated with differences in the rate of earnings growth. The results were broadly similar across the sub-periods 1997-2001 and 2001-2004.
Keywords: 330